Where do we go in terms of safety and quality of obstetric care in Colombia? (Colombia Medica, 2016)
Despite the great achievements in indicators of access to prenatal care and delivery care with qualified staff in Latin America, the fifth goal agreed at the Millennium Development Goals (MDG 5) of reducing maternal mortality in 75% by 2015 did not come true. In part, this can be explained by gains in coverage that do not result in safe and high quality obstetric care.Extreme Maternal Morbidity (EMM), defined as a serious complication that occurs during pregnancy, childbirth and postpartum, and which threatens the life of a woman, is an anticipatory event of death. Its monitoring enables identification of actions that prevent maternal death, and therefore it is recognized as a quality tracer; Colombia, with the establishment of monitoring extreme maternal morbidity (EMM) at national level, have the opportunity to become a model country in how to improve obstetric care.This implies improving the skills of human resources in the analysis of cases, properly interpreting the indicators generated from their surveillance, and developing and implementing improvement plans in line with the needs of the institutions involved in obstetric care, making emphasis on quality and safety of care.